Organic/inorganic hybrid nanoparticulate resonant contrast agents - Kramberger, I (2016)
An intriguing frontier for magnetic resonance imaging (MRI) is the development of responsive Gd3+-based contrast agents (CAs) that can report physiological variations in the tissue microenvironment.[1] Heterogeneous biological milieu and quantification of the CA concentration at the site of interest are the major limitations of responsive concentration-dependent protic MRI probes. A ratiometric approach based on dualmode CAs containing a 19F MRI reporter, in addition to a paramagnetic moiety, is one of the feasible strategies to overcome this drawback. Since high fluorine content is required for in vivo imaging, nanoparticles offer advantageous characteristics over molecular probes due to their large surface area and size, allowing the incorporation of high concentrations of uorinated probes and paramagnetic CAs. For emerging applications of Gd3+ complexes at ultra-high magnetic fields, it was found that not only octadentate (q = 1), but also highly kinetically stable nonadentate (q = 0) Gd3+-DOTA systems can be incorporated into the mesopores of silica nanoparticles, resulting in an 8-fold increase in proton longitudinal relaxivity from 0.7 mM-1 s-1 to 6.2 mM-1 s-1 at 4.7 T compared to their molecular counterparts. A further 7-fold increase in longitudinal relaxivity was achieved when the silica surface of such particles was functionalised with highly acidic propyl sulphonates, enabling faster proton transfer through a hydrogen-bonded hydronium network. pH responsiveness of Gd3+ complexes tethered to particles has, on the other hand, been achieved through either local mobility or water access regulated by pH-responsive polymers acting as gating valves on the mesopores. Moreover, symmetric 19F MRI CAs were accommodated within micron- and nanosized matrices comprised of polyelectrolytes, quaternary ammonium first generation dendrimers and centrifugable oil-containing silica nanocapsules. For these, the biggest challenge has been posed by restricted local mobility, which notably shortens transverse relaxation time and attenuates the 19F NMR signal. Finally, polymers based on uorinated quaternary ammonium, pH-sensitive and Gd3+-DOTA methacrylates were prepared, exhibiting a dual 19F/1H MRI contrast with reverse pH response.